Effects of elementary school neighbourhood environment on children's play activities: a case study of GaeMyong elementary school neighbourhood - Lee, Woo Min; Park, Hyo Sook; Kim, Seung Nam; Kim, Jae Cheol; Lee, Kyung Hwan (International Journal of Urban Sciences, 2020)
Although play activity is essential for children, opportunities for play is decreasing due to changes in life patterns. Urban neighbourhoods should be part of the provision of space where children can play freely and should help children play as part of their daily routine. This study analysed the elementary school neighbourhood environment features influencing the play activity of children. Study results showed that traffic safety, crime safety, walking environment, and community consciousness influenced the activity of children. It was also found that children tended to play adventurously, such as climbing up to a high position on a handrail or jungle gym and walking atop high places. This study will help to promote the play activity of children through improving an elementary school neighbourhood environment by focusing on the features that affect children's play activity.